Penerapan Interdisipliner Terhadap Penyelesaian Nusyuz Guna Menciptakan Keharmonisan Dalam Keluarga - Alfarisi, Andi; Putra, Adji Pratama (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2023)
The disputes that occur in the marriage are a problem that must be faced by every couple in the family. One of them is the occurrence of nusyuz that carried out by one of the partners, especially for couples who have been going on for a long time. This problem is feared to result in dharar if not resolved immediately. The purpose of this paper is to examine a problem with an interdisciplinary approach that elaborates two or more methods, data, techniques, theories, or perspectives in answering a problem that is more context-adaptive, as well as knowing how to apply interdisciplinary methods in studying a problem. This type of research is field research with an interdisciplinary approach that uses two theories: first, the nash grouping theory. Second, symbolic interactionism. In this research, it can be concluded that the concepts that were born from the combination of theories in this paper include; First, in grouping the nash objectively intend to perpetuate a marriage, temporally provide several sanctions as a settlement step and provide